Quranic Manuscripts In The First Century Of Hijrah - Mokhtar, Ahmad Baha'; Abdul Rahman, Ahmad Abdussalam; Abdul Aziz, Hanan; b. Ibrahim, Muhammad Lukman; b. Ibrahim, Muhammad Lukman (Jurnal KIAS, 2020)
In this modern and sophisticated era, the access to copies of al-Quran is easily available and owned and the need to old Quranic manuscripts is less popular. Nonetheless, the old manuscripts are not regarded as merely exhibitional sources at the library. Its importance is equally significant and these manuscripts should be thoroughly studied because old Quranic manuscripts possess its own high value in delivering the knowledge of Quranic Calligraphy as a primary source in the rasm Uthmani. This paper will discuss parts of the copies of Quranic manuscripts which were written in the first Islamic century. In this study, the writer will try to review the copies of manuscripts which were written in the early history of Islam. Its present status will also be examined and in the final study, the comparison between the old manuscripts and the present mushaf will be discussed. The outcome of the study on the manuscripts proves the truthfulness of Allah's promise towards preserving al- Quran and rejects the false perceptions of disbelievers of al-Quranic text authenticity. This study aims to collect informations related to Quranic manuscripts and present its outcome. According to the researcher's findings, the writing of the Quranic manuscripts during the period of Prophet Muhammad S.A.W and the Uthmani Mushaf written during the period of Caliph Uthman r.h. were lost and unable to be traced. However, presently the manuscripts written within the first century of Hijrah are still intact and available.